HLA-DRB1 alleles in juvenile-onset systemic lupus erythematosus: renal histologic class correlations - B.L. Liphaus; M.H.B. Kiss; A.C. Goldberg (Brazilian Journal of Medical and Biological Research, 2007)
Human leukocyte antigens (HLA) DRB1*03 and DRB1*02 have been associated with systemic lupus erythematosus (SLE) in Caucasians and black populations. It has been observed that certain HLA alleles show stronger associations with SLE autoantibodies and clinical subsets, although they have rarely been associated with lupus renal histologic class. In the present study, HLA-DRB1 allele correlations with clinical features, autoantibodies and renal histologic class were analyzed in a cohort of racially mixed Brazilian patients with juvenile-onset SLE. HLA-DRB1 typing was carried out by polymerase chain reaction amplification with sequence-specific primers using genomic DNA from 55 children and adolescents fulfilling at least four of the American College of Rheumatology criteria for SLE. Significance was determined by the chi-square test applied to 2 x 2 tables. The HLA-DRB1*15 allele was most frequent in patients with renal, musculoskeletal, cutaneous, hematologic, cardiac, and neuropsychiatric involvement, as well as in patients positive for anti-dsDNA, anti-Sm, anti-U1-RNP, and anti-SSA/Ro antibodies, although an association between HLA alleles and SLE clinical features and autoantibodies could not be observed. The HLA-DRB1*17, HLA-DRB1*10, HLA-DRB1*15, and HLA-DRB1*07 alleles were significantly higher in patients with renal histologic class I, class IIA, class IIB, and class V, respectively. The present results suggest that the contribution of HLA- DRB1 alleles to juvenile-onset SLE could not be related to clinical or serological subsets of the disease, but it may be related to renal histologic classes, especially class I, class II A, class II B, and class V. The latter correlations have not been observed in literature.